PERANCANGAN INSTALASI LISTRIK GEDUNG DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA ( P2KB) PROVINSI SULAWESI TENGAH - Yusuf Yusuf; Agustinus Kali; Yulius S. Pirade (Foristek, 2020)
Electricity has become a basic need for various human activities, because electricity has functions and benefits that are vital in daily life which has become a basic need in encouraging national development in all fields. One part of the world electricity is the installation of lighting that is also me njadi one of the main points in a building, it is very necessary that human activity has remained secure and running smoothly. In this study, the writer will design an electrical installation for a building, namely the office building of the Population and Family Planning Control Office (P2KB) of Central Sulawesi Province, JL. RA Kartini NO. 100 Palu City. This study aims to make an electrical installation design in accordance with the Indonesian National Standard (SNI) and the General Electrical Installation regulations (PUIL), so that the installation is designed to be more effective and efficient. In the design of this installation also made design drawings for installation in buildings. Based on the design planning of the electrical installation that has been done, the results are obtained, the total electrical power from the electrical installation of this building is 60246 watts or 75307 VA and for electricity supply is taken from PLN, namely 3-phase electricity with a capacity of 82,500 VA. The conductor used in this installation uses NYY and NYM cable types. The security used in this installation consists of 2 types, namely NFB and MCB , in addition to this building installation system is also given a PHB box to facilitate maintenance and repair in case of damage. Taking into account the economic and safety factors of the installation, the total Budget Plan (RAB) for the installation of the building of the Population and Family Planning Control Office (P2KB) is Rp. 223,600,000